The fragments of the Methodists - Tecușan, Manuela. (Studies in Ancient Medicine, 2004)
The Fragments of the Methodists is a new attempt to give a first corpus of its kind. Manuela Tecusan has collected, edited, and translated all the surviving testimonials concerning one of the most influential 'schools' or doctrines of medicine in late antiquity: Methodism. This volume contains the fragments accompanied by a textual apparatus and facing English translation. The introduction provides a guide to the collection. The second volume presents a commentary to all fragments and two glossaries of medical and pharmacological terms. Apart from its intrinsic novelty, this material affords fresh insights into broad topics of contemporary concern, such as the relation between philosophy and medicine, problems of biomedical ethics, the epistemological foundations of the sciences, the role of causal explanation - explored here in their fascinating historical set-up. Many of the long texts included in the Methodist collection become now available in a translation for the first time.